Answer:
5
Step-by-step explanation:
2x - y when x = 0 and y = -5
2(0) - (-5) =
= 0 + 5
= 5
Answer:
Step-by-step explanation:
Let f(x) be denoted by y,thus y= -3x+2
Now interchange x and y,it becomes x= -3y+2
Solve for y,
y
=
2
−
x
3
This is
f
−
1
x
Step-by-step explanation:
-2 x 3/7 = (-2 x 3) /7
= -6/7
We know that vertically opposite angles are equal.
So, k = 131° [Vertically opposite angles]
and g = 43° [Vertically opposite angles]
We know that linear pair of angles are supplementary (180°).
So, h + 43° = 180° [Linear pair of angles]
=> h = 180° - 43°
=> h = 137°
and m + 131° = 180° [Linear pair of angles]
=> m = 180° - 131°
=> m = 49°
By the way I looked this up but heres the best ive got
<span>Simplifying
(-1x + 27) + (16x + 4) = 0
Reorder the terms:
(27 + -1x) + (16x + 4) = 0
Remove parenthesis around (27 + -1x)
27 + -1x + (16x + 4) = 0
Reorder the terms:
27 + -1x + (4 + 16x) = 0
Remove parenthesis around (4 + 16x)
27 + -1x + 4 + 16x = 0
Reorder the terms:
27 + 4 + -1x + 16x = 0
Combine like terms: 27 + 4 = 31
31 + -1x + 16x = 0
Combine like terms: -1x + 16x = 15x
31 + 15x = 0
Solving
31 + 15x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-31' to each side of the equation.
31 + -31 + 15x = 0 + -31
Combine like terms: 31 + -31 = 0
0 + 15x = 0 + -31
15x = 0 + -31
Combine like terms: 0 + -31 = -31
15x = -31
Divide each side by '15'.
x = -2.066666667
Simplifying
x = -2.066666667</span>